Thermal degradation and pyrolysis analysis of zinc borate reinforced intumescent fire retardant coatings - Gillani, Q.F. (Elsevier B.V., 2018)
This work aims at evaluating the potential of nano-sized zinc borate as substitution of boric acid for thermal degradation and gaseous products in expandable graphite based intumescent fire retardant coating IFRC systems. The thermal degradation and pyrolysis of intumescent flame retardant coatings was characterized by bunsen burner fire test, thermogravimetric analysis (TGA), field emission scanning electron microscopy (FESEM), energy dispersive spectrometry (EDX), X-ray diffraction (XRD), fourier transformed infra-red analysis (FTIR), X-ray photoelectron spectroscopy (XPS) and gaseous emission analysis (Py-GC). Bunsen burner fire test reveals that the partial substitution of zinc borate (6.61 mass) imparts a substantial improvement in thermal stability and reduces steel substrate temperature to 124 °C. From thermogravimetric analysis results, it was shown that this composition increases char residual mass from 39 to 46.14 mass. The morphological structures of char residue were investigated by FESEM and it indicates that zinc borate promotes more continuous and compact char layers that hinder the heat diffusion and oxygen transmission effectively. XRD and FTIR results show that zinc borate develops a zinc-based glassy intumescent shield i.e. zinc bis (hydroxyanthrapyrimidine) dehydrate (C30H14N4O4Zn·2H2O) that strengthens the char. The new chemical species enhances the thermal stability of the freshly formed char at high temperature and provides an enhanced fire protection. XPS analysis shows the higher carbon contents in formulation IF-5 (6.6 mass) and endorses high char residue. The Py-GC analysis confirms release of less toxic gaseous products in IF-5 formulation, considering their type and concentration, as compared to control formulation, and is considered as an environmentally safe intumescent formulation. © 2018